THE IMPACT OF DATA SECURITY ON THE INTENTION OF VIETNAMESE CONSUMERS TO USE E-WALLETS - Thi Thu Huong Hoang; Hoang Nam Vu; Thi Khanh Chi Nguyen (Tạp chí Khoa học Đại học Đà Lạt)
E-wallets are used as a form of payment that brings many benefits to users. This article studies the impact of data security on consumer intentions to use e-wallets in the rapidly growing economy of Vietnam. The data consist of 236 observations from a survey of consumers in Vietnam. Covariance-based structural equation modeling (CB-SEM) was employed to test the proposed hypotheses. Research results show that security trust has the greatest impact on the intention to use e-wallets, followed by perceived privacy risk, social influence, and information sensitivity. The study also reveals the role of privacy policies and security concerns in consumer intentions to use e-wallets. Based on the research results, the study provides recommendations for consumers, e-wallet providers, and governmental agencies to increase awareness of and responsibility for information security among the consumers who use e-wallets.